THE CONCEPT “OUTSTANDING PERSONALITY” AND UNIVERSITY ENVIRONMENT: A SYMBOLIC-DIDACTIC SENSE OF A DESTINY (P.A. Sorokin and L.P. Karsavin) - D. N. Bezgodov; E. A. Vologin (Высшее образование в России, 2017)
The article explores the function of the concept “outstanding personality” in the realization of the educational potential of the University internal environment, identified in the article with the educational environment. The concept of educational environment in turn is considered as equivalent to the concept of organizational culture of an educational institution. The personalities of Pitirim Sorokin and Lev Karsavin are closely associated with the history of Komi Region and their heritage falls into a context of the mission and educational environment of Ukhta State Technical University.